Smartphone Learning Media Prototype Model Based on SAC (Smart Apps Creator) For 4.0 Learning - Puspitasari, Jerry; Juhadi, Juhadi; Suyahmo, Suyahmo; Wijayanto, Pradika Adi; Saadah, Nuris (International Journal of Social Learning (IJSL), 2022)
Smartphone-based learning media is an alternative for developing learning media that can infiltrate the limitations of space and time. This study aimed to determine the effectiveness of smartphone media for learning in the 4.0 era from media developed using the SAC (Smart Apps Creator) application. This research and development type uses the Hannafin & Peck design model. The research subjects used a purposive sample technique from 35 students of class XI IPS 3 SMA Jepon, Blora Regency, Central Java. Data analysis using Mixed Methods, data obtained by filling out checklists, questionnaires, and filled tests to conclude its effectiveness. Based on the research results, SAC (Smart Apps Creator) media is fun, easy to understand, interesting, practical, and not boring. The level of complete learning reached 91.4%. Students become accustomed to using technology 4.0 in learning, so they are expected to develop critical, creative, communicative, and collaborative thinking.